NEUROMODULATING EFFECT OF DUNALIELLA SALINA EXTRACT IN THE REGRESSION OF ALZHEIMER'S DISEASE IN RATS - FAROUK K. EL-BAZ,; HANAN F. ALY,; GAMILA H. ALI, (International Journal of Pharma and Bio Sciences, 2016)
The current study was undertaken to elucidate a possible neuromodulating role of Dunaliella salina ethanolic extract (150 mg /g b.w. daily for one month) against the development of Alzheimer’s disease (AD) in experimental rat model. Alzheimer’s disease was produced in male rats by intraperitoneal injection of AlCl3 (4.2 mg/kg b.w.) daily for one month. After treatment the oxidative stress biomarkers; nitric oxide (NO), malondialdehyde (MDA), and antioxidant enzymes; glutathione reduced (GSH), superoxide dismutase (SOD) and catalase activities, ATPase, apoptotic marker and caspase-3 were assayed. Also, brain cholinergic marker, acetylcholine esterase (ACHE), noradrenaline (NA), adrenaline (A), dopamine (DA), serotonin (5-HT) were determined. The results revealed significant increase in oxidative stress biomarkers associated with significant decrease in the antioxidant enzymes activity in Alintoxicated rats. Significant depletion in brain ATPase enzyme activity while, significant increase in caspase-3 activity was detected. Moreover, significant elevations in brain ACHE activity accompanied with significant reduction in DA, NA, A, 5-HT levels were recorded. Marked amelioration was detected in all investigated neurological biomarkers upon treatment of AD rats with D. salina extract in comparison with Donepezil reference drug. These results were confirmed by histological examination of brain sections. Hence, the current results clearly indicated neuromodulating effect of D. salina against Alzheimer’s disease.